LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

Semaji - Black Community Resource Centre (BCRC) (2017)
Number of pages: 10

Forecaster - Coasters Association (2017)
Number of pages: 6

Lower North Shore Tourism Report 2017 - Coasters Association (2017)
Over the period of January 28th to August 28th, a “Junior Tourism & Communications Consultant” was contracted by the Coasters Association, through a project with Emploi Quebec, to work with the Lower North Shore Tourism Ad Hoc Table. This contract included the following objectives: • Training (Coaching); • Implementation of the tourism action plan; • Marketing actions; • Support to entrepreneurs; • LNS Tourism Forum. In addition to these objectives, the Junior Tourism & Communications Consultant was mandated to work on the Coasters Association’s project with Canada Economic Development (refer to Section II of the report), which included the implementation of the tourism marketing actions, and the coordination and planning of the upcoming Lower North Shore Tourism Forum 2017.

Flowers : An Anthology - Dawson Alternative; Writers in the Community (2017)
Number of pages: 25

Network News - Quebec Community Groups Network (QCGN) (2017)
Number of pages: 9

General By-Laws of The 4 Korners Family Resource Centre - 4Korners (2017)

Improving the Spectrum of Services Offered to English-Speaking Seniors : CIUSSS de la Capitale-Nationale’s Experience Implementation Project: 2014-2018 - Paquette, Brigitte (2017)
issued: November 23, 2017/November 24, 2017 Number of Pages : 35

News from the Evidence Base : Findings from the 2016 Census of Canada - Pocock, Joanne (2017)
Keywords: Official Language Minority Community (OLMC)

Provision of Services by English-Speaking Agent - Vienney, Annie; Dufour, Claudiane; Sullivan, Sharleen (2017)

The Coasters Association and Community Vitality on the Lower North Shore of Québec - Maurice, Cornella (Coasters Association, 2017)
Vital communities are characterized by strong, active and inclusive relationships between residents, private sector, public sector and civil society organizations that work to foster individual and collective wellbeing. Vital communities are those that are able to cultivate and marshal these relationships in order to create, adapt and thrive in a changing world and thus improve wellbeing of citizens
Keywords: Official Language Minority Community (OLMC)

Community Leaders Ready to Assist Kathleen Weil, Quebec's New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

Semaji - Black Community Resource Centre (BCRC) (2017)
Number of pages: 10

Report on the Health and Social Services Priorities of English-speaking Communities in Quebec - Carter, James; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
In July 2017, the CHSSN submitted the present report to the Quebec Ministry of Health and Social Services inviting it to undertake consultations with key public institutions and community representatives with respect to the recommendations. The objective was to ensure that a proposal to Health Canada reflected the shared commitment of Quebec and its English-speaking communities to work in partnership to improve access to health and social services in English. In its reply to the CHSSN in October 2017 (Appendix), the Ministry supported the recommendations in accordance with comments reflecting the results of its consultations with the public institutions. To support Health Canada in its mandate to prepare a new Contribution Program, the sponsoring organizations of the twenty recognized community health and social services networks along with the CHSSN are submitting the present report and recommendations reflecting the continuity of results of the last federal contribution and emergence of new priorities for the period ahead.
Keywords: Official Language Minority Community (OLMC)

Community Matters - Montérégie West Community Network (MWCN) (2017)
Number of pages: 4

Network News - Quebec Community Groups Network (QCGN) (2017)
Number of pages: 14

QCGN Project to Involve Youth in Canada's Sesquicentennial - Quebec Community Groups Network (QCGN) (2017)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)
Number of pages: 10

QCGN Welcomes Nomination of Kathleen Weil as Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 10

Turn into YES 12 : A Benefit Event and Silent Auction : Sponsorship Opportunity - Youth Employment Services (YES) (2017)

Five Inspiring Community Leaders to be Honoured by QCGN - Quebec Community Groups Network (QCGN) (2017)

Final Report: Emploi Quebec: Coasters Association - Gallibois-Robertson, Melanie (Coasters Association, 2017)

QCGN Congratulates New MUHC Board and Pledges its Support - Quebec Community Groups Network (QCGN) (2017)

QCGN Mourns the Loss of Gretta Chambers, une Grande Dame of Quebec - Quebec Community Groups Network (QCGN) (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

Semaji - Black Community Resource Centre (BCRC) (2017)
Number of pages: 10

Language Training Program : Report on interviews with health and social services network respondents - Farley, Roger (Dialogue McGill, 2017)

KIDS Summer Camp 2017 - Keats, Shannon A. (Coasters Association, 2017)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. From 2008 to 2016 the five camps were in operation and ran very well.

Community Matters - Montérégie West Community Network (MWCN) (2017)
Number of pages: 4

A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 9

Resources for Families with Special Needs - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Action Plan : Westhaven Neighborhood Committee - Westhaven Neighborhood Committee (2017)

Program Book for Winter/Spring 2017 - Youth Employment Services (YES) (2017)
issued: January, 2017/August, 2017

Community Looks Forward to MUHC Resolution - Quebec Community Groups Network (QCGN) (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 6

Forecaster - Coasters Association (2017)
Number of pages: 8

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 10

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)
Number of pages: 10

Bell Media Must Restore Local Sports at CTV Montreal : QCGN - Quebec Community Groups Network (QCGN) (2017)

Composite Indicators for Community Vitality - Estrie (QC) - Floch, William; Abou-Rjeili, Elias; Durand, Martin (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes Creation of New Secretariat in Premier's Office - Quebec Community Groups Network (QCGN) (2017)

QCGN Looks Forward to Champion for All Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

Annual General Meeting of West Quebecers : 2016-2017 - Regional Association of West Quebecers (RAWQ) (2017)

QCGN Pledges Constructive, Positive Role in Process Launched Today by Premier - Quebec Community Groups Network (QCGN) (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 7

Semaji - Black Community Resource Centre (BCRC) (2017)
Number of pages: 10

The Mother Hood - Dawson Alternative School (2017)
Number of pages: 34

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 4

Annual Activity Report : June 1, 2016 - May 31, 2017 - Literacy Quebec (LQ) (2017)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once via conference call for professional development and networking opportunities. Through a PACTE funded project, Literacy Quebec was able to develop tools to strengthen its network. The project allowed us to examine new ways of promoting literacy and explaining the issues surrounding low literacy to the general public. The project also enabled the organization to engage more volunteers and pilot a database to track volunteers, supporters, members, etc.

QCGN Invites Meilleur to Become Acquainted with English-speaking Quebec - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Shares Concerns Over Selection Process for Commissioner of Official Languages - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

Policy for Use of the Dynamic Signage System / Politique d'utilisation du système d'écrans dynamiques - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Let's Shift the Focus to Underlying Issues at McGill University Health Centre - Quebec Community Groups Network (QCGN) (2017)

[Quality of Life Conference] - NDG Community Council (NDGCC) (2017)

Presentation by Youth Employment Services (YES) to the Standing Senate Committee on Official Languages and the English-speaking Community in Quebec - Youth Employment Services (YES) (2017)
YES (Youth Employment Services) is a non-for-profit charity whose mission is to enrich the community by providing English-language services to help people find jobs and start small and medium size businesses.
Keywords: Official Language Minority Community (OLMC)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

Community Matters - Montérégie West Community Network (MWCN) (2017)
Number of pages: 4

Poetry - Perspectives I (2017)
Number of pages: 33

Employment in the Québec Regions : Needs Assessment Study - Youth Employment Services (YES) (2017)
The current needs assessment was developed with the vision of understanding the socioeconomic conditions of seven Quebec regions examined by this study, namely, Gaspésie-Îles-de-la-Madeleine, Capitale-Nationale, Chaudière-Appalaches, Estrie, Montérégie, Côte-Nord and Abitibi-Témiscamingue. The study also involved conducting an inventory of job search and employment-related services in these seven Québec regions, and identifying the needs of English-speaking job seekers residing in the regions. The intent of this study is to inform the development of timely, evidence-based English-language employment services and career supports in the regions, ultimately leading to increased economic opportunities and stability for English-speaking youth (aged 16-35) in Québec. A related goal is to increase awareness of English-language employment services and supports available to job seekers in the Québec regions.

73rd Annual General Meeting & Awards Banquet - Quebec Federation of Home and School Associations (QFHSA) (2017)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2017)
Parallel title: Education in the 21st Century : The First 20 Years

Resolution 2017-02 : Diversity and Inclusion - Quebec Federation of Home and School Associations (QFHSA) (2017)

Resolution 2017-04 : Quebec Secondary III and IV History Curriculum: In Need of Change - Quebec Federation of Home and School Associations (QFHSA) (2017)

Software Coding : Resolution 2017-05 - Quebec Federation of Home and School Associations (QFHSA) (2017)

Annex - List of Funded Projects - Quebec Community Groups Network (QCGN) (2017)

Social Initiatives to Address Needs of Vulnerable English-speaking Youth, Seniors and Newcomers - Quebec Community Groups Network (QCGN) (2017)

Tradition Allows MNA Coiteux to Speak English in National Assembly - Quebec Community Groups Network (QCGN) (2017)

French Language Study Program : Immigration and Education Officials Need to Find Solution, Not Cast Aspersions on Students and English School Boards - Quebec Community Groups Network (QCGN) (2017)

Quebec Community Groups Network Brief to House of Commons Standing Committee on Official Languages : Full Implementation of the Official Languages Act in the Canadian Justice System - Quebec Community Groups Network (QCGN) (2017)
The Quebec Community Groups Network (QCGN) is pleased to submit the following brief to the House of Commons Standing Committee on Official Languages’ (LANG) study on the Full Implementation of the Official Languages Act in the Canadian Justice System. We understand the Committee’s objective is to examine how and to what extent the Official Languages Act is applied in areas of justice that fall under federal jurisdiction. The Committee should know that English-speaking Quebec does not yet possess the level of capacity in this sector represented by organizations like the Fédération des associations de juristes d'expression française de common law, the Centre canadien de français juridique, or the Réseau national de formation en justice. We do not have researched and coherent policy proposals, nor even a developed Quebec-wide network of English-speaking jurists. We are hopeful however that this capacity will develop, and the QCGN continues to actively support the newly formed Association of English-speaking Jurists of Quebec (AESJQ), who have submitted their own brief towards this study.
Keywords: Official Language Minority Community (OLMC)

Lower North Shore Collective Impact Forum - Coasters Association (2017)
In April 2017, the Commission Scolaire du Littoral and Community Learning Centres hosted a Lower North Shore training forum. The goal of this regional training forum was to provide an opportunity for participants to learn a method of working together called “Collective Impact”. Collective impact is an advanced method of collaboration that teaches participants how to work together to solve large complex problems so that schools and communities may thrive, developing shared success and shared leadership. Complex problems require engagement and collaborative leadership of stakeholders from across all sectors and all levels of the community leadership including i.e. government leaders, funding agencies, schools, hospitals, the private sector, the not-for-profit sector, community organizers and community members.

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 5

Health and Social Services Community Leadership Bursary Program : Annual report - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2017)
This document is the second annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program.1 It aims to present data related to bursaries awarded for the 2014-2017 period, based on data collected during the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. The report also provides a profile of graduate recipients for whom post- graduation follow-up was required during the period covered. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Health and Social Services Community Leadership Bursary Program : Bi-annual report - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2017)
This document is the third bi-annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program. This report aims to present data related to bursaries awarded for the 2014-2017 period, taking into account the recipients’ situation as of the second semester of the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Application for Public Reading(s) by English-language Writers Published by AELAQ Members : Funded by the Canada Council for the Arts - Association of English-language Publishers of Quebec (AELAQ) (2017)

Presentation to the Committee on Culture and Education on Bill 86 - Duszara, Walter; Chambers, Geoffrey; Maldoff, Eric; Martin-Laforge, Sylvia (2017)

Response to ELAN Member and Community Questions for Simon Brault - English Language Arts Network (ELAN); Canada Council for the Arts (2017)

QCGN Hopeful About Opportunities for Official Language Minority Communities in Federal Budget - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

Opportunities & Obstacles Facing English-Speaking Newcomers Launching Small to Medium Enterprises (SMEs) in Quebec - Association for Canadian Studies (2017)
The objective of this research study is to identify the key barriers and opportunities that English-speaking newcomers face when launching or planning to launch small to medium enterprises (SMEs) in Quebec. We intend to use the information gathered by this study to assist policy makers and entrepreneurship service providers in supporting newcomers (recent immigrants who arrived in the past five years) in the creation and growth of SMEs, leading to a stronger entrepreneurial society and economy in Quebec.

Bursary Program - Neighbours Regional Association of Rouyn-Noranda (2017)

QCGN to Host Conference on Community Engagement and the Integration of Newcomers - Quebec Community Groups Network (QCGN) (2017)

Bilingual Young Quebecers Leading the Way to Canada's Future - Quebec Community Groups Network (QCGN) (2017)

[Letter to M. Sebastien Proulx, Minister of Education] - Lemay, Diane (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 6

Indigenous Education : Walking on Both Sides of the River - Advisory Board on English Education (2017)
Worldwide research has identified low school achievement levels among students from Indigenous cultures and there is a gradual movement to improve their situation. The Truth and Reconciliation Commission (TRC) of the Canadian government has provided the impetus for the provinces to examine their practices and the Advisory Board on English Education (ABEE) congratulates the Minister of Education, Recreation and Sports for joining this initiative. The research literature and the media have identified a broad range of issues affecting the success of Indigenous children in schools. Some of these issues, such as the remoteness and inaccessibility of the communities, poverty, the scarcity and high cost of food, poor housing, and infrastructure problems, are outside the scope of educational solutions, although they combine to have a profound effect on educational outcomes. Social and medical services must be called upon to improve the circumstances that contribute to the educational success of Indigenous students, and we hope this will be facilitated in Québec by the provincial government’s Aboriginal Social Development Action Plan. Yet education is fundamental to any potential solution to Indigenous concerns and problems, and any changes to the situation of the 100 000 Indigenous people of Québec must start with the younger generation. Many of the issues affecting the students and their success or failure in school can be addressed by the school system and this brief will identify some of them. In no way is this brief a prescription to “cure problems” in the Indigenous school system, so it does not contain recommendations, unlike most ABEE briefs. Rather, we will identify some of the issues that might contribute to the discussion of Indigenous education in Québec. We hope that some of the observations and recommendations we have made in earlier briefs regarding the Anglophone school system will be useful additions to the conversation, even though our perspective is influenced by differences between cultures and long-standing problems within Indigenous school systems.

Semaji - Black Community Resource Centre (BCRC) (2017)
Number of pages: 8

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Parallel title: Improving the Health and Well-Being of English-Speaking Magdalen Islanders
Keywords: Official Language Minority Community (OLMC)

Tourism 2025 : CEDEC's Plan for Creating 46,900 Jobs and Adding $5.2 Billion to the Economy - Community Economic Development and Employability Corporation (CEDEC) (2017)

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands 2017-2020 - Community Health and Social Services Network (CHSSN); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Committee for Anglophone Social Action (CASA) (2017)
The official language minority community of this region has the poorest socioeconomic status in Canada when aspects such as low education levels, unemployment and low income tendencies are analyzed. Children are particularly affected by this status. Children ages 0 to 5 make up 6.6% of the total English-speaking population.
Keywords: Official Language Minority Community (OLMC)

Spring Newsletter - Regional Association of West Quebecers (RAWQ) (2017)
Number of pages: 12

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)
Number of pages: 10

Welcome to Saint Brigid’s Home Residential and Long Term Care Center : Welcome Guide for Residents and their Loved Ones - Jeffery Hale - Saint Brigid's (JHSB) (2017)

The Network Model : Influencing Public Policy for Social Change - Community Health and Social Services Network (CHSSN) (2017)
The case studies being presented in today demonstrate that the development principles are at work every day and are now being pressed into new areas of action. The values underpinning the network model include promoting the identity of our communities, promoting social inclusion and advocating for equity in the broader society in its treatment of communities. These values can support network strategies to enter the “next level” of participation in societal initiatives setting broad policy goals. The reward for such effort can be societal recognition that the programs that define Quebec’s commitment to social progress also include our communities.

Access to Public Long-term Care : Useful information for seniors and their loved ones - Jeffery Hale Community Services (2017)

QCGN Welcomes Resurrection of Independent Court Challenges Program - Quebec Community Groups Network (QCGN) (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 7

Community Matters - Montérégie West Community Network (MWCN) (2017)
Number of pages: 4
Keywords: Official Language Minority Community (OLMC)

Community Matters - Montérégie West Community Network (MWCN) (2017)
Number of pages: 4

Saint Brigid's Residents' Committee : Welcome to Your Home! / Saint Brigid's Comité des résidents : Bienvenu(e) chez vous ! - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 2

[Newsletter] - 4 Korners Family Resource Center (2017)
Number of pages: 4

The CLC Guidebook : Steps to Development - Smith, William J.; Leading English Education and Resource Network (LEARN) (2017)

Annual Report : 2016-2017 - 4Korners (2017)

Health Passport : When Language Matters / Passport santé : Question de langue - Assistance and Referral Centre (ARC) (2017)

Active Offer : A Culture of Respect, a Culture of Excellence - Canada. Office of the Commissioner of Official Languages (2017)

Plan d'action touristique Basse-Côte-Nord du Québec / Lower North Shore Tourism Plan - Coasters Association (2017)

Répit et soutien aux aides-soignant / Respite and Support for Caregivers - Coasters Association (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2017)
Number of pages: 5

Community NetLink - Community Health and Social Services Network (CHSSN) (2017)
Number of pages: 8

Mobilizing / se Mobilisent - Community Health and Social Services Network (CHSSN) (2017)

2016-2017 Funded Projects - Dialogue McGill (2017)

Dialogue : Better Communication for Better Care - Dialogue McGill (2017)
Number of pages: 4

Dialogue : Better Communication for Better Care - Dialogue McGill (2017)
Number of pages: 6

13th Annual AGM Motions for Discussion - English Language Arts Network (ELAN) (2017)

Culture in the Schools - Application Guide - English Language Arts Network (ELAN) (2017)

Proposed Fee Structure: Pay What You Can (PWYC) - English Language Arts Network (ELAN) (2017)

David Graham - Graham, David (2017)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2017)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2017)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2017)
issued: Winter, 2017/Winter, 2018

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Fostering Health and Well-Being in Education - Leading English Education and Resource Network (LEARN) (2017)
Number of pages: 351

Teaching With Technology : Pedagogical Possibilities and Practicalities - Leading English Education and Resource Network (LEARN) (2017)
Number of pages: 244

Society Pages - Morrin Centre (2017)
Number of pages: 16

Society Pages - Morrin Centre (2017)
Number of pages: 16

Society Pages - Morrin Centre (2017)
Number of pages: 16

Society Pages - Morrin Centre (2017)
Number of pages: 16

Annual Report : 2016–2017 - NDG Community Council (NDGCC) (2017)

NDG : A snapshot : Quality of life conference / NDG : Un aperçu : 2017 conférence sur la qualité de vie - NDG Community Council (NDGCC) (2017)

Rapport annuel : 2016–2017 - NDG Community Council (NDGCC) (2017)

Demographic Profiles of English-speaking Communities in RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches (1210) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS Alphonse-Desjardins (1211) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de Beauce (1213) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de la région de Thetford (1212) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS de Rouyn-Noranda (0813) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS du Témiscaming (0815) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS Vallée-de-l'Or (0814) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Hochelaga - Mercier-Ouest - Rosemont (0653) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Rivière-des-Prairies - Anjou - Montréal-Est (0652) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Saint-Léonard - Saint-Michel (0651) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS d'Asbestos (0517) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Coaticook (0514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de la Haute-Yamaska (0512) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de la Pommeraie (0511) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Sherbrooke (0514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Val Saint-François (0516) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS du Granit (0519) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS du Haut-Saint-François (0518) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie & RLS de Memphrémagog (0513) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Dorval - Lachine - Lasalle (0612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Pierrefonds - Lac Saint-Louis (0611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de Grande-Rivière - Hull - Gatineau (0714) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de la Vallée-de-la-Gatineau (0712) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de la Vallée-de-la-Lièvre et de la Petite-Nation (0715) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS des Collines-de-l'Outaouais (0713) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS du Pontiac (0711) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Portneuf (0311) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Québec-Sud (0312) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS Québec-Nord (0313) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de Kawawachikamach (0917) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de la Basse-Côte-Nord (0916) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de la Haute-Côte-Nord - Manicouagan (0912) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de Sept-Îles (0914) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS d'Arthabaska-de l'Érable (0418) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Bécancour - Nicolet-Yamaska (0416) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Drummond (0417) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Trois-Rivières (0415) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Centre-de-la-Mauricie (0414) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Haut-Saint-Maurice (0411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre (1610) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre & RLS du Haut-Richelieu - Rouville (1612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est (1620) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS de Richelieu-Yamaska (1622) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS Pierre-Boucher (1621) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS Pierre-de Saurel (1623) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest (1630) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Jardins-Roussillon (1634) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Vaudreuil-Soulanges (1631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Haut-Saint-Laurent (1633) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Suroît - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière (1410) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière & RLS de Lanaudière-Nord (1411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière & RLS de Lanaudière-Sud (1412) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Laval (1310) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides (1510) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Antoine-Labelle (1511) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Argenteuil (1514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Deux-Montagnes - Mirabel-Sud (1515) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de La Rivière-du-Nord - Mirabel-Nord (1516) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Thérèse-de Blainville (1517) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Laurentides (1512) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Pays-d'en-Haut (1513) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Bas-Saint-Laurent & RLS de Rimouski (0115) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-des-Neiges - Métro - Parc-Extension (0622) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-Saint-Luc - NDG - Montréal-Ouest (0621) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS de Verdun - Côte St-Paul - St-Henri - Pointe-St-Charles (0631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS des Faubourgs - Plateau-Mont-Royal - St-Louis-du-Parc (0632) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS d'Ahuntsic - Montréal-Nord (0642) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS de la Petite Patrie - Villeray (0643) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS du Nord de l'Île - Saint-Laurent (0641) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de Chicoutimi (0215) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de Jonquière (0214) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de La Baie (0216) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Annual Report / Rapport annuel 2016-2017 - Quebec Community Groups Network (QCGN) (2017)

Leading the Way / Prendre les commandes - Quebec Community Groups Network (QCGN) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)
Number of pages: 24

Annual Report : 2016-2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 8

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 7

2016-17 Annual Report - The English Speaking Catholic Council (ESCC) (2017)

Annual Report 2016/2017 - Townshippers' Association (2017)

Annual Report - Vision Gaspé-Percé Now (VGPN) (2017)

Annual Report - Vision Gaspé-Percé Now (VGPN) (2017)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

Fall 2017 : Program Book : September 2017 - December 2017 - Youth Employment Services (YES) (2017)